(3EXgGQ GdYUQ dCSQGQ Ggd GdYUQs - (3CHi GdMSf EHQGgje Hf YeQ Hf GdQHGW GdHbGYi GdTGaYjs; (3GHf MLQ GdYSbdGfj,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jHOF hjYjO hjfTF hjHjO , hHYO agPG JGQjN TjNfG TjN GdCSdGe CHhGdaVd Hf MLQ s
(3BNQgG (B:s
(3hjhe GdKdGKGA dKdGKjf ef Pi GdMLg ai GMOi YTQ aHbi Ydjg ef Jhajbg GdRQGY GdSGOSI YTQ Ydi cd TF bOjQ Cejf hGab GdaQGZ ef gPG GdOjhGf s
(3GdfSNI HgG MhGTs
(3Pjd Hg JGQjN TjNg GHf MLQ GdYSbdGfi GdeSei (B: (3EfHGA GdZeQ HGHfGA GdYeQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdJGQjNs